Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the coefficients and the constant term of the quadratic equation [tex]\(0=2+3x^2-5x\)[/tex], we need to compare it to the standard form of a quadratic equation, which is [tex]\(ax^2 + bx + c = 0\)[/tex].
### Step-by-Step Solution
1. Identify the term corresponding to [tex]\(a\)[/tex]:
- The term involving [tex]\(x^2\)[/tex] in the equation is [tex]\(3x^2\)[/tex]. Therefore, the coefficient [tex]\(a = 3\)[/tex].
2. Identify the term corresponding to [tex]\(b\)[/tex]:
- The term involving [tex]\(x\)[/tex] in the equation is [tex]\(-5x\)[/tex]. Therefore, the coefficient [tex]\(b = -5\)[/tex].
3. Identify the constant term [tex]\(c\)[/tex]:
- The constant term in the equation is [tex]\(2\)[/tex]. Therefore, [tex]\(c = 2\)[/tex].
Summarizing these values, we have:
[tex]\[a = 3\][/tex]
[tex]\[b = -5\][/tex]
[tex]\[c = 2\][/tex]
So, the coefficients and constant term for the equation [tex]\(0 = 2 + 3x^2 - 5x\)[/tex] are:
[tex]\[ \begin{aligned} &a = 3 \\ &b = -5 \\ &c = 2 \end{aligned} \][/tex]
### Step-by-Step Solution
1. Identify the term corresponding to [tex]\(a\)[/tex]:
- The term involving [tex]\(x^2\)[/tex] in the equation is [tex]\(3x^2\)[/tex]. Therefore, the coefficient [tex]\(a = 3\)[/tex].
2. Identify the term corresponding to [tex]\(b\)[/tex]:
- The term involving [tex]\(x\)[/tex] in the equation is [tex]\(-5x\)[/tex]. Therefore, the coefficient [tex]\(b = -5\)[/tex].
3. Identify the constant term [tex]\(c\)[/tex]:
- The constant term in the equation is [tex]\(2\)[/tex]. Therefore, [tex]\(c = 2\)[/tex].
Summarizing these values, we have:
[tex]\[a = 3\][/tex]
[tex]\[b = -5\][/tex]
[tex]\[c = 2\][/tex]
So, the coefficients and constant term for the equation [tex]\(0 = 2 + 3x^2 - 5x\)[/tex] are:
[tex]\[ \begin{aligned} &a = 3 \\ &b = -5 \\ &c = 2 \end{aligned} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.